An Empirical Case Study of Kraft Foods (IPO) & Kyber Network (ICO) - Alom , Shahedin (South Asian Journal of Social Sciences and Humanities, 2022)
In order to advise investors, who are choosing the appropriate avenue to invest between Kyber Network and Kraft Foods, this study investigates the platforms under which these two companies perform in the capital markets. These platforms are the Initial Public Offering [IPO] and Initial Coin Offering [ICO]. In order to find the most appropriate option, both platforms were studied on how they have developed over time. Various principles and requirement guiding their different uses and application were furthermore studied to provide insights on what a potential investor may be required in order to venture into these platforms. These findings were critical in proceeding to further find out how Kyber Network and Kraft Food have embraced these differences. Kyber Network trades in ICO while Kraft Food trades in IPO. In aspects of profitability, this study found out that Kyber Network has more prospective profitability with time due to increasing in per crypto price. Kraft Food’s per share price is declining hence it’s not profitable. In floating process, Kyber Network was found to be simpler and efficient for users since it only needs a user to create an account and begin trading with their crypto currencies or crypto tokens. Though Kyber Network was found to carry higher risk in the aspect of cyber risk, basic etiquettes of securing one’s online information would address any cyber risk. Henceforth, this study finds that investing in Kyber Network ICO is more profitable for investors.